Reproductive performance and economic value of does in different broiler breeders of rabbit under semi arid conditions* - Pannu, Urmila; Beniwal, K; Singh, V K; Gahlot, R S (The Indian Journal of Animal Sciences, 2005)
The data of 5 broiler breeds of rabbit were analyzed to study the effect of various genetic and non-genetic factors on litter size and weight at birth and weaning, gestation length and kindling interval. The overall least-squares means were estimated as 6.1 ± 0.011, 5.2 ± 0.10, 335.8 ± 03.15 g, 2724.1 ± 059.83 g, 31.3 ± 0.86 days, 104.0 ± 4.83 days and Rs 646.8 ± 14.07 for litter size and weight at birth and weaning, gestation length, kindling interval and economic value ofdoes respectively. Breed had significant effect on all litter traits and economic value and non-significant effect on gestation length and kindling interval. Year of kindling had highly significant effect on all reproductive traits and economic value except gestation length that was significant. The effect of litter size at birth was highly significant on litter size at weaning and litter weight at birth and weaning and effect of parity order was highly signiticant on all traits except gestation length. Dam’s weight at mating also had significant effect on all traits except litter weight at birth. The reproductive performance of White Giant rabbits was better than other breeds. The estimates of heritability for all reproductive traits were moderate with high standard errors, except litter weight at weaning; the high heritability indicated more impact of genctic factors. The genetic and phenotypic correlations of litter size at birth were positive and high with litter weight and litter size at weaning and negative genetic correlations were found with litter weight at weaning, gestation length and kindling interval. Litter weight at birth was genetically negatively correlated with other traits except litter weight at weaning. Other correlaions were generally negative.